Apple of the Empire: Landscape and Imperial Identity in Turn-of-the-Century British Columbia - Bennett, Jason (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractWith the dawn of a new century, the British Empire faced the world with a new monarch as the Dominion of Canada braced for one of the largest immigration movements in its brief history. These currents of change also mirrored broader societal transformations marked by dramatic industrial expansion and exploding urban growth. In this period of great transition, many well-to-do Britons found a powerful antidote to their fears and insecurities in the far-away province of British Columbia. Aggressively promoted by private land developers, immigrants found affinity with a radically-altered landscape defined by the agricultural practice of fruit farming. Representing a wealth of finance, culture, and refinement, notions of the land animated and perpetuated the values and identity of the new community. Although these settlers were eager to exclude difference and achieve a “natural” balance with nature, the intertwining of landscape and Empire could not preclude change, nor exorcise its own profound flaws.